RISK FOR POSTTRAUMATIC STRESS DISORDER ASSOCIATED WITH DIFFERENT FORMS OF INTERPERSONAL VIOLENCE IN SOUTH AFRICA - Kaminer, Debra (2008)
The South African population is exposed to multiple forms of violence. Using nationally representative data from 4,351 South African adults, this study examined the relative risk for posttraumatic stress disorder (PTSD) associated with political, domestic, criminal, sexual and other (miscellaneous) forms of assault in the South African population. Violence exposure was assessed using the ‘worst event’ list from the WHO’s Composite International Diagnostic Interview (CIDI) and a separate questionnaire assessing experiences of human rights abuses, and lifetime PTSD was assessed according to the APA’s Diagnostic and Statistical Manual of Mental Disorders criteria using the CIDI. Findings indicated that over a third of the South African population has been exposed to some form of violence. The most common forms of violence experienced by men were criminal and miscellaneous assaults, while physical abuse by an intimate partner, childhood physical abuse and criminal assaults were most common for women. Among men, political detention and torture were the forms of violence most strongly associated with a lifetime diagnosis of PTSD, while rape had the strongest association with PTSD among women. At a population level, criminal assault and childhood abuse were associated with the greatest number of PTSD cases among men, while intimate partner violence was associated with the greatest number of PTSD cases among women. Recommendations for mental health service provision in South Africa and for future research on the relative risk for PTSD are offered.